Some features of teaching the Russian language to foreign students of technical universities with an engineering profile (Journal of Science-Innovative Research in Uzbekistan, 2024)
The article discusses some features of teaching the Russian language to foreign audiences at technical universities, pays attention to the selection of material, the choice of reading texts used in practical classes, and characterizes the individual specifics of perception and presentation of the material.